2019
DOI: 10.1037/trm0000161
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious trauma, themes in research, and terminology: A review of literature.

Abstract: Growth in the arena of trauma-informed care has correspondingly created interest in the potential hazards for clinicians who regularly provide trauma-based services. However, what to call the phenomena of clinicians being affected by bearing witness to other's trauma is a source of perplexity. A review of research indicated numerous terms are being used to describe this phenomenon. The literature review looked specifically at the term vicarious trauma, first developed by McCann and Pearlman (1990), and other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(135 citation statements)
references
References 31 publications
4
116
0
6
Order By: Relevance
“…This hypothesis was supported by the data, which showed that child welfare professionals' vicarious trauma significantly and positively predicted levels of professional burnout. This finding complements previous research showing that job burnout and distress resulting from traumatic content among individuals working in human service professions are related (see Branson, 2019;Fansher et al, 2019). These data also suggest that there is a need to address the issue of vicarious trauma in order to reduce levels of professional burnout among the child welfare and early childhood workforce.…”
Section: Aim 1: Direct Effect Of Vicarious Trauma On Professional Bursupporting
confidence: 85%
See 4 more Smart Citations
“…This hypothesis was supported by the data, which showed that child welfare professionals' vicarious trauma significantly and positively predicted levels of professional burnout. This finding complements previous research showing that job burnout and distress resulting from traumatic content among individuals working in human service professions are related (see Branson, 2019;Fansher et al, 2019). These data also suggest that there is a need to address the issue of vicarious trauma in order to reduce levels of professional burnout among the child welfare and early childhood workforce.…”
Section: Aim 1: Direct Effect Of Vicarious Trauma On Professional Bursupporting
confidence: 85%
“…The child welfare and early childhood workforce faces numerous difficulties in their unique line of work, and one noteworthy work-related obstacle is vicarious trauma. Vicarious trauma (also called secondary traumatic stress or compassion fatigue; Branson, 2019;Vrklevski & Franklin, 2008) refers to a cumulative process of cognitive changes due to exposure to the experiences of traumatized clients that results in disruptions to identity, worldview, and beliefs about trust and safety (Branson, 2019;Canfield, 2005;McCann & Pearlman, 1990). When professionals seek to internally process or make meaning out of traumatic content instead of working out the meaning of difficult work experiences in a structured and safe environment with another professional such as a supervisor, they are more likely to experience vicarious trauma (McCann & Pearlman, 1990;Regehr, Hemsworth, Leslie, Howe, & Chau, 2004;Vrklevski & Franklin, 2008).…”
Section: Vicarious Trauma: Definition Prevalence and Negative Effectsmentioning
confidence: 99%
See 3 more Smart Citations